MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM NASARI - Oktapiani, Sarita; Asriati, Nuraini; Khosmas, FY (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis entitled "Analysis of Compensation In Increasing Employees Productivity At Cooperative Loan Nasari". The purpose of this study is to know: 1) Implementation of compensation, 2) Working productivity of cooperative employees, 3) provision of compensation in increasing work productivity.The research method used in this research is descriptive method. The form of research is case study. The author uses data collection techniques in the form of direct communication techniques and documentary studies. Data collection tools used in the form of interview guides and documents. Results of the study States that (1) The enactment of the awarding of compensation that is in the cooperative loan Nasari has been cooperative with the ability to adapt, (2) Employee Productivity high KSP Nasari It is seen from a comparison of the productivity index (IP) average of 0.20, and provides facilities to support the work of the employees, as well as paying attention to the needs of the employee but does not harm employees and employees provide labor productivity as a consequence the maximum over the compensation received. (3) the granting of compensation to the employee cooperative administrators can increase the level of productivity of 4.05. Keywords: Provision of Compensation, Work Productivity, Cooperative Employee